Routine coagulation tests on ICU admission are associated with mortality in sepsis: an observational study. Issue 7 (6th July 2017) - Benediktsson, S.; Frigyesi, A.; Kander, T.
Abstract : Background: Low platelet count on admission to an intensive care unit (ICU) is associated with increased mortality and is thus included in some severity scoring systems such as the simplified acute physiologic score 3 (SAPS 3); however it is unclear whether other routine coagulation tests also predict mortality. The purpose of this retrospective single‐centre study was to investigate whether activated partial thromboplastin time (APTT) or prothrombin time – international normalized ratio (PT‐INR) measured on admission to the ICU in patients with severe sepsis or septic shock may be associated with mortality independent of SAPS 3 score. Methods: All patients admitted to a tertiary general ICU from 2007 to 2014 diagnosed with severe sepsis or septic shock were eligible. Results from APTT and PT‐INR within 1.5 h of admission as well as SAPS 3 were used as independent variables in a Cox regression. Results: Of total 5485 ICU admissions during the study period we identified 647 unique patients with severe sepsis or septic shock. APTT and PT‐INR were found to correlate significantly with mortality with a hazard ratio (HR) of 1.014 [95% confidence interval of HR (1.006–1.023)] for APTT and 1.422 (1.117–1.811) for PT‐INR. HR for SAPS 3 was 1.036 (1.028–1.044). Conclusion: Activated partial thromboplastin time prolongation and raised PT‐INR on ICU admission in patients with severe sepsis or septic shock is associated with increased mortality independent of SAPS 3 score. This indicates that APTT prolongation and PT‐INR increase represents morbidity that is not accounted for in SAPS 3.